KALIY O‘G‘ITLARI ISHLAB CHIQARISHDA TUZ TASHLAMALARI VA CHIQINDI OMBORLARINI REKULTIVATSIYA QILISH - Yarboboev, T.N.; Qosimova, K.Y. (SCIENCE and SOCIETY, 2025)
The production of potash fertilizers is one of the developing industries today. Any branch of the mining industry, including the production of potash fertilizers, has its own impact on the environment in a certain sense. The article briefly analyzes the negative environmental impact of a large amount of waste generated during the extraction and processing of potash ores, research work carried out on the reclamation of waste storage. Based on the results of the analysis, the technology of recultivation of the waste storage facility of JSC “Dehkanabad Potash Plant” was recommended.
Keywords: environment; salt waste; halite; silvinite; reclamation; waste storage; mining industry; clay-salt sludge; mine; flotation; quarry